Between the Sacred and the Profane: Poblana Identity in the First Half of the 19th Century - Marín Ibarra, Mariana (2021)
This article starts from the concept of «memory-heritage» which is built through three basic channels: language, education and institutions. In the city of Puebla, the Church and the City Council relied on these channels to form citizens who are socially and morally religiously useful. Through these speeches, a collective memory was generated that began to rely on images that defended its patriotism, thus historically outstanding figures such as Iturbide or the Virgin of Guadalupe appeared, images that were part of the pantheon of national and local celebrations, becoming references of identity and educational of the angelopolitan population.